Automatization of incident categorization - Silva, Sara Alexandra Teixeira da (2019)
To be able to keep up with the grow of the created incidents quantity in an organization nowadays, there was the need to increase the resources to ensure the management of all incidents. Incident Management is composed by several activities, being one of them, Incident Categorization. Merging Natural Language and Text Mining techniques and Machine Learning algorithms, we propose improve this activity, specifically the Incident Management Process. For that, we propose replace the manual sub-process of Categorization inherent to the Incident Management Process by an automatic sub-process, without any human interaction. The goal of this dissertation is to propose a solution to categorize correctly and automatically the incidents. For that, there are real data provided by a company, which due to privacy questions will not be mention along dissertation. The datasets are composed by incidents correctly categorized, which leverage us to apply supervised learning algorithms. It is supposed to obtain as output a developed method through the merge of Natural Language Processing techniques and classification algorithms with better performance on the data. At the end, the proposed method is assessed comparatively with the current categorization done to conclude if our proposal really improves the Incident Management Process and which are the advantages brought by the automation.